2007
DOI: 10.1128/jb.00387-07
|View full text |Cite
|
Sign up to set email alerts
|

Differential Interaction ofAggregatibacter(Actinobacillus)actinomycetemcomitansLsrB and RbsB Proteins with Autoinducer 2

Abstract: Our previous studies showed that the Aggregatibacter actinomycetemcomitans RbsB protein interacts with cognate and heterologous autoinducer 2 (AI-2) signals and suggested that the rbsDABCK operon encodes a transporter that may internalize AI-2 (D. James et al., Infect. Immun. 74:4021-4029, 2006.). However, A. actinomycetemcomitans also possesses genes related to the lsr operon of Salmonella enterica serovar Typhimurium which function to import AI-2. Here, we show that A. actinomycetemcomitans LsrB protein comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 41 publications
1
78
0
2
Order By: Relevance
“…If exogenous autoinducer-2 or a functional luxS gene carrying plasmid is added in the growth medium, normal growth of the biofilm is restored (28). Two periplasmic receptors for autoinducer-2, LsrB and RbsB, were also identified and it was observed that if one or both receptors are inactivated, biofilm growth was either reduced, or completely disabled (29). The fact that Aggregatibacter actinomycetemcomitans also responds to a broad range of autoinducer-2 concentration, is a subject of scientific discussion and further research since the aforementioned periplasmic receptors show different kinetics of interaction with the autoinducer.…”
Section: Quorum Sensing I Regulacija Drugih Funkcijamentioning
confidence: 99%
See 3 more Smart Citations
“…If exogenous autoinducer-2 or a functional luxS gene carrying plasmid is added in the growth medium, normal growth of the biofilm is restored (28). Two periplasmic receptors for autoinducer-2, LsrB and RbsB, were also identified and it was observed that if one or both receptors are inactivated, biofilm growth was either reduced, or completely disabled (29). The fact that Aggregatibacter actinomycetemcomitans also responds to a broad range of autoinducer-2 concentration, is a subject of scientific discussion and further research since the aforementioned periplasmic receptors show different kinetics of interaction with the autoinducer.…”
Section: Quorum Sensing I Regulacija Drugih Funkcijamentioning
confidence: 99%
“…Ako se u medij za rast doda egzogeni autoinduktor-2 ili plazmidi koji nose funkcionalni luxS gen, omogućeno je normalno formiranje biofilma (28). Identificirana su dva periplazmička receptora za autoinduktor-2 -LsrB i RbsB te je uočeno, ako se inaktivira jedan ili oba, formirani biofilm bit će manji, odnosno njegova će formacija biti potpuno onemogućena (29). Predmet je znanstvene rasprave i daljnjih istraživanja reagira li doista Aggregatibacter actinomycetemcomitans na raspon različitih koncentracija autoinduktora-2, s obzirom na to da prije spomenuti periplazmički receptori pokazuju različitu kinetiku interakcije s autoinduktorom.…”
Section: Plančak I Surunclassified
See 2 more Smart Citations
“…Agregatinobacter actinomycetemcomitans and Haemophilus influenzae use other type of receptors as well for the sensing of AI-2s, the RbsB proteins, which have high homology (above 70%) with the ribose ABC transporter (38,39).…”
Section: Peptide-type Autoinducersmentioning
confidence: 99%